Expression of Long Interspersed Nuclear Element 1 Retroelements and Induction of Type I Interferon in Patients With Systemic Autoimmune Disease. Issue 11 (27th October 2016) - Mavragani, Clio P.; Sagalovskiy, Irina; Guo, Qiu; Nezos, Adrianos; Kapsogeorgou, Efstathia K.; Lu, Pin; Liang Zhou, Jun; Kirou, Kyriakos A.; Seshan, Surya V.; Moutsopoulos, Haralampos M.; Crow, Mary K.
Abstract : Objective: Increased expression of type I interferon (IFN) and a broad signature of type I IFN–induced gene transcripts are observed in patients with systemic lupus erythematosus (SLE) and other systemic autoimmune diseases. To identify disease‐relevant triggers of the type I IFN pathway, this study sought to investigate whether endogenous virus‐like genomic repeat elements, normally silent, are expressed in patients with systemic autoimmune disease, and whether these retroelements could activate an innate immune response and induce type I IFN. Methods: Expression of type I IFN and long interspersed nuclear element 1 (LINE‐1; L1) was studied by polymerase chain reaction, Western blotting, and immunohistochemistry in samples of kidney tissue from patients with lupus nephritis and minor salivary gland (MSG) tissue from patients with primary Sjögren's syndrome (SS). Induction of type I IFN by L1 was investigated by transfection of plasmacytoid dendritic cells (PDCs) or monocytes with an L1‐encoding plasmid or L1 RNA. Involvement of innate immune pathways and altered L1 methylation were assessed. Results: Levels of L1 messenger RNA transcripts were increased in lupus nephritis kidneys and in MSG tissue from patients with SS. Transcript expression correlated with the expression of type I IFN and L1 DNA demethylation. L1 open‐reading frame 1/p40 protein and IFNβ were expressed in MSG ductal epithelial cells and in lupus nephritis kidneys, and IFNα was detected in infiltrating PDCs. Transfection of PDCs or monocytes with L1‐encoding DNA or RNA induced type I IFN. Inhibition of Toll‐like receptor 7 (TLR‐7)/TLR‐8 reduced the induction of IFNα by L1 in PDCs, and an inhibitor of IKKε/TANK‐binding kinase 1 abrogated the induction of type I IFN by L1 RNA in monocytes. Conclusion: L1 genomic repeat elements represent endogenous nucleic acid triggers of the type I IFN pathway in SLE and SS and may contribute to initiation or amplification of autoimmune disease.